To find the missing number in the equivalent expressions \( 15 + 9 = ?(5 + 3) \), we can first simplify the right side of the equation.
First, calculate \( 5 + 3 \): \[ 5 + 3 = 8 \]
Now we replace this in the equation: \[ 15 + 9 = ? \times 8 \]
Next, calculate \( 15 + 9 \): \[ 15 + 9 = 24 \]
So now the equation looks like this: \[ 24 = ? \times 8 \]
To find the value of \( ? \), we can divide both sides of the equation by 8: \[ ? = \frac{24}{8} = 3 \]
Thus, the missing number in the expression is \( 3 \). Therefore, the complete expression is: \[ 15 + 9 = 3(5 + 3) \]